El Caracol en Su Laberinto: Migración y Transformación Social - El Caso de los Colombianos en Aragón (España) (The Snail in Its Labyrinth: Migration and Social Change - The Case of Colombian Citizens in Aragon (Spain)) - Yulieth Teresa Hillón (Oñati Socio-Legal Series)
This work is a micro analysis of the possibilities of social transformation that human action can generate in contexts of unequal power. Based on the theoretical framework of the power and the symbolic violence of Law, migration chains and networks and travel and transformation of collective imaginaries, this research studies two interlinked processes, using the case of Colombian residents in Aragon (Spain). On one hand, it aims to explain and understand how Law builds a particular subject (called the "Immigrant") trying to reach specific political, economic, social and identitarian goals. Also, it tries to discover the degree of mobility and activity that migrants can handle due to the legal and social circumstances in which they live. Both processes will help us to comprehend how migration policies affect Spaniards and foreigners (in their interaction with different kind of legal frameworks as well as in their relations among themselves), how some transnational spaces work and how some strategies created or used by foreigners can become active resistance tools for human development.